Classical antiquity and medieval Ireland an anthology of medieval Irish texts and interpretations - Clarke, Michael 1950-; Poppe, Erich 1951-; Torrance, Isabelle ca. 20./21. Jh (Bloomsbury Academic, 2024)
"This ... book fills a huge gap in the study of classical reception in Irish literature by making accessible in translation selections from a wide variety of C10th-C15th texts. These texts are important because they demonstrate Ireland's indigenous and pre-colonial expertise in classical learning. Ireland thus emerges as a unique case in postcolonial terms where classical education is normally assumed to derive from a British imperial model"--
Keywords: Rezeption; Mittelirisch; Antike; Latein; Literatur; Irish literature / Middle Irish, 1100-1550 / Classical influences; Irish literature / To 1100 / Classical influences; Irish literature / Middle Irish, 1100-1550 / Texts; Irish literature / To 1100 / Texts; Literature, Medieval / History and criticism; Littérature médiévale / Histoire et critique; Littérature irlandaise / 1100-1550 (Moyen irlandais) / Influence ancienne; Littérature irlandaise / 1100-1550 (Moyen irlandais) / Textes; Littérature irlandaise / Jusqu'à 1100 / Influence ancienne; Littérature irlandaise / Jusqu'à 1100 / Textes; Anthologie